Slow-wave activity saturation and thalamocortical isolation during propofol anesthesia in humans. - Ní Mhuircheartaigh, R; Warnaby, C; Rogers, R; Jbabdi, S; Tracey, I (2013)
The altered state of consciousness produced by general anesthetics is associated with a variety of changes in the brain's electrical activity. Under hyperpolarizing influences such as anesthetic drugs, cortical neurons oscillate at ~1 Hz, which is measurable as slow waves in the electroencephalogram (EEG). We have administered propofol anesthesia to 16 subjects and found that, after they had lost behavioral responsiveness (response to standard sensory stimuli), each individual's EEG slow-wave activity (SWA) rose to saturation and then remained constant despite increasing drug concentrations. We then simultaneously collected functional magnetic resonance imaging and EEG data in 12 of these subjects during propofol administration and sensory stimulation. During the transition to SWA saturation, the thalamocortical system became isolated from sensory stimuli, whereas internal thalamocortical exchange persisted. Rather, an alternative and more fundamental cortical network (which includes the precuneus) responded to all sensory stimulation. We conclude that SWA saturation is a potential individualized indicator of perception loss that could prove useful for monitoring depth of anesthesia and studying altered states of consciousness.